Recombinant soluble type I interferon receptor exerts antiviral activity by inducing proteins related to autophagy - Aliaga-Gaspar, Pablo; Brichette Mieg, Isabel; Fernández-Arjona, María del Mar; Rodríguez-Bada, José Luis; Lopez-Moreno, Yolanda; Serrano-Castro, Pedro Jesús; Fernández Fernández, Oscar; Ciano-Petersen, Nicolas Lundahl; Oliver-Martos, Begoña (Elsevier, 2024)
The soluble type I IFN receptor (sIFNAR2) is produced by alternative splicing and is present in body fluids. Although it can modulate IFN-ß activity, its biological role remains unknown. Methods: An in-silico study was conducted to compare the structure of recombinant human soluble IFNAR2 (r sIFNAR2) with its native form. The antiviral activity of r-sIFNAR2, produced in BL21-bacteria and CHO cells, was tested using a cytopathic effect assay including appropriate controls. Viability and toxicity were assessed by MTT assays. Proteomic analysis using mass spectrometry was conducted in the A549/EMCV bioassay to elucidate the mechanism of action, and then it was validated by Western blot. Results: The BL21-sIFNAR2 had a sequence identity of 83.6 % with the native form, showing variations only in terminal regions. BL21-sIFNAR2 and CHO-sIFNAR2 showed significantly higher percentage of cell viability compared to the viral control, similar to IFN-ß. Cell viability with BL21-sIFNAR2 was comparable to the cell control across all tested concentrations. Proteomic analysis revealed an up regulation of pathways related with autophagy (macroautophagy, autophagy, pexophagy, and mitophagy) with an SQSTM1 overexpression that was then confirmed by Western Blot, espe cially after virus infection. However, pathways related to interferon signaling, and antiviral mechanisms mediated by IFN-stimulated genes were down-regulated. Conclusion: r-sIFNAR2 exhibits significant antiviral activity regardless of the expression system used for its production and good safety profile, suggesting its use as a potential antiviral drug. Proteins related to autophagy are involved in the protection from the virus. This study highlights the biological relevance of soluble cytokine receptors as effectors so far overlooked
Keywords: Farmacología; Medicina; Interferón; Receptores celulares; Soluble interferon beta receptor; Recombinant protein; Antiviral activity